Work place frustration induced dissatisfaction behaviour among public school teachers in Akinyele local government area of Oyo state (2020)
This study examines workplace frustration-induced dissatisfaction behaviours among teachers in Public Secondary Schools in Akinyele Local Government Area of Oyo State the lackadaisical attitudes of the public secondary school teachers in Nigeria which affect their output as perceived by the researcher informed the decision to investigate into the rationale for the gross dissatisfaction in the workplace of these employees. Teachers play a key role in the educational transformation of any nation either developing or developed The survey research design was adopted with a sample of 150 respondents spanned across ten selected schools. The data collecting Instruments was a semi-structured questionnaire. The analysis was done, using Statistical Package for the Social Sciences Version 21 (SPSS 21) Hypothesis one shows that there was significant effect of perceived adequacy and regularity of salary payment on job dissatisfaction F (2,147) = 6.61, p<.0.l Hypothesis two shows that there was significant effect of perceived adequacy and quality of facilities (infrastructure) on job dissatisfaction F (3,147) = 3.38. p<.05. Hypothesis three shows that there was significant effect of job motivation on job dissatisfaction F (2,147) = 13.24, p<.OI. This study concludes by recommending that teachers' satisfaction is germane for the sustainability of good learning environment for good performance of the students in schools